The procedure for determining the number of measurements in the normalization of random error of an informationmeasuring system with elements of artificial intelligence - Cherepanska, Iryna; Bezvesilna, Olena; Sazonov, Artem; Nechai, Sergii; Khylchenko, Tetiana (Eastern-European Journal of Enterprise Technologies, 2017)
Features of estimation and normalization of random components of the errors occurring in measurements with the help of goniometric systems were considered. A general procedure has been formulated that makes it possible to soundly determine the necessary and sufficient number of measurement repetitions to ensure accuracy and reliability of the obtained results. The procedure is based on application of mathematical apparatus of the probability theory, mathematical analysis and statistics, as well as the assumption that random errors obey the normal law of distribution of random quantities. Operatioability of the proposed procedure and effectiveness of its use have been experimentally confirmed. In particular, when comparing the obtained results with those in a similar work [7], the time taken to carry out measurements decreased by 1.3 times. That is, the effect of applying the proposed procedure is greater than the measurement costs while a high accuracy of 0.01 and reliability of 0.95 are maintained. The obtained results indicate the possibility of further extensive laboratory and industrial applications